Design and evaluation of floating microspheres of amoxicillin trihydrate by ionotropic gelation method - Chakrabotry, S.; Dey, B. K.; Saha, S.; Kar, A.; Saha, B. (Journal of Applied Pharmaceutical Research, 2014)
The purpose of this investigation was to design and develop floating microspheres of Amoxicillin Trihydrate by ionotropic gelation method with combination of two polymers and to get the best possible formulation out of that with the various aspects. Floating drug delivery system have a bulk density less than gastric fluids and so remains buoyant in the stomach without affecting gastric emptying rate for a prolonged period of time. The floating microspheres were prepared using Ethyl cellulose and Hydroxy propylmethyl cellulose K4M as polymer to achieve an extended retention in upper GIT and there by improved bioavailability. The microspheres were evaluated for particle size analysis, Drug Entrapment Efficiency, Drug Loading Capacity, Floating efficiency, Swelling Study, Loose Surface Crystal Study , drug entrapment efficiency, drug- polymer compatibility study, Micromeritic properties like Bulk Density, Tapped Density, Carr’s Index, and Hausner’s Ratio, In-vitro release studies and surface morphology characterized by Scanning electron microscopy (SEM). The Microspheres have an average size range of 743.00±7.000 to 837.00±8.544μm. The entrapment efficiency was found to be in the range of 66.96±1.944 to 82.03±0.657 %. The In-vitro release studies of the drug from the best formulation F6 exhibited a sustained release of 93.46±0.684 % as studied over 10hrs. Release was best explained by zero-order kinetics model and it shows that the drug release follows diffusion mechanism. FT-IR data revealed that, compatible and there was no interaction between the drug and excipients added in the formulation. The data obtained in this study thus suggest that a floating microspheres of Amoxicillin Trihydrate are promising for sustained drug delivery which can reduce dosing frequency.